Reconstruction of the glenoid using autologous bone-graft and the SMR Axioma TT metal-backed prosthesis: the first 45 sequential cases at a minimum of two years' follow-up. (December 2018) - Malhas, A. M.; Granville-Chapman, J.; Robinson, P. M.; Brookes-Fazakerley, S.; Walton, M.; Monga, P.; Bale, S.; Trail, I.
Abstract : Aims: We present our experience of using a metal-backed prosthesis and autologous bone graft to treat gross glenoid bone deficiency. Patients and Methods: A prospective cohort study of the first 45 shoulder arthroplasties using the SMR Axioma Trabecular Titanium (TT) metal-backed glenoid with autologous bone graft. Between May 2013 and December 2014, 45 shoulder arthroplasties were carried out in 44 patients with a mean age of 64 years (35 to 89). The indications were 23 complex primary arthroplasties, 12 to revise a hemiarthroplasty or resurfacing, five for aseptic loosening of the glenoid, and five for infection. Results: Of the 45 patients, 16 had anatomical shoulder arthroplasties (ASA) and 29 had reverse shoulder arthroplasties (RSA). Postoperatively, 43/45 patients had a CT scan. In 41 of 43 patients (95%), the glenoid peg achieved > 50% integration. In 40 of 43 cases (93%), the graft was fully or partially integrated. There were seven revisions (16%) but only four (9%) required a change of baseplate. Four (25%) of the 16 ASAs were revised for instability or cuff failure. At two-year radiological follow-up, five of the 41 cases (11%) showed some evidence of lucent lines. Conclusion: The use of a metal baseplate with a trabecular titanium surface in conjunction with autologous bone graft is a reliable method of addressing glenoid bone defects in primary and revision RSA setting in the short term. ASAs have a higher rate of complications with this technique.